Аналіз економічної сутності землі як об'єкта оподаткування - Павлій, О.С. (Економіка промисловості, 2014)
Стаття присвячена аналізу економічної сутності землі як об’єкта оподаткування. Особливу увагу приділено розгляду землі з точки зору її багатофункціонального використання. Проаналізовано особливості землі як просторового базису для розміщення житлового та народного господарства, об’єкта купівлі-продажу, а також головного засобу виробництва у сільському господарстві. Статья посвящена анализу экономической сущности земли как объекта налогообложения. Особое внимание уделено рассмотрению земли с точки зрения её многофункционального использования. Проанализированы особенности земли как пространственного базиса для размещения жилищного и народного хозяйства, объекта купли-продажи, а также основного средства производства в сельском хозяйстве. The article is devoted to the analysis of land value taxation which is an important direction of the overall tax system. The main target of the paper is to consider the economic essence of the land as the object of taxation. It is also important to pay attention to the difference between such terms as "land", "land parcel" and "land resources" that are used as identical, although in fact they have certain differences.The analysis of scientific publications of domestic and foreign economists and researchers on the issue of land value taxation has been conducted in the article. A special attention is given to the consideration of land in terms of its multifunctional use. Characteristics of the land as spatial basis for location of housing services and sectors of the national economy, the object of sale and means of production have been analyzed. Particular attention is given to the characteristics of land as real estate. Considering the land as a commodity the comparative analysis of market and area-based assessment of the land has been performed. The advantages and disadvantages of both ways of land valuation have been identified. The essence of the land market and factors that influence its formation has also been determined. The features of land as means of production have also been reviewed. The essence of such terms as "land", "land parcel" and "land resources" have been considered according to the law of Ukraine.It is summed up that on the one hand, land is a natural resource, which is characterized by space, topography, soils, flora and fauna, and evaluated from a position of multifunctional performance that is not always related to the income. On the other hand, the land is considered as an integral and essential part of any real estate property and is assessed in terms of its utility and profitability. Thus the land is a complicated object of taxation, the economic essence of which is revealed in the use of the land by entities that have ownership of it defined by the laws.